Association between adolescent tobacco, alcohol and illicit drug use and individual and environmental resilience protective factors. Issue 11 (25th November 2016) - Hodder, Rebecca Kate; Freund, Megan; Bowman, Jenny; Wolfenden, Luke; Gillham, Karen; Dray, Julia; Wiggers, John
Abstract : Objectives: Research suggests that individual and environmental resilience protective factors may be associated with adolescent substance use; however, the associations between a broad range of such factors and use of various types of substances have not been examined. The study aimed to determine the association between a comprehensive range of adolescent individual and environmental resilience protective factors and measures of tobacco, alcohol and illicit substance use. Design: Cross-sectional study. Setting: 32 Australian secondary schools. Participants: Grade 7–10 students (aged 11–17 years). Measures: Data regarding 14 student individual and environmental resilience protective factors and seven substance use measures (tobacco, alcohol, marijuana, other illicit drug use) were obtained via an online self-report survey. Adjusted multivariate logistic regression analyses examined the association between all student resilience protective factors and seven substance use measures. Results: Inverse univariate associations were found for 94 of 98 relationships examined (n=10 092). Multivariate analyses found: consistent inverse associations between 2 of 14 protective factors and all substance use measures ('goals and aspirations', 'prosocial peers'); inverse associations between 4 protective factors with multiple substance use measures ('home support' (5 of 7), 'school support' (3 of 7), 'self-awareness' (2 of 7), 'community meaningful participation' (2 of 7)); positive associations between 2 resilience protective factors with multiple measures of substance use ('community support' (3 of 7), 'peer caring relationships' (5 of 7)) and 6 protective factors not to be associated with any substance use measure. Conclusions: Despite individual relationships between the majority of resilience protective factors and substance use types, the protective benefit of such factors for adolescent substance use was limited to only a small number of such factors when considered collectively. Such results suggest that interventions seeking to reduce adolescent substance use may need to target specific protective factors to address specific types of substance use. Trial registration number: ACTRN12611000606987, Results.